Pengaruh Return on Assets, Return on Equity, Net Profit Margin, Dan Debt to Equity Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2017-2021 - Fitri Umuni’matin Nada; Rendra Erdkhadifa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine the effect of Return on Assets, Return on Equity, Net Profit Margin, Debt to Equity on profit growth in manufacturing companies listed on the BEI in 2017-2021. This research method uses an associative quantitative approach. The sampling technique used was purposive sampling, resulting in 14 manufacturing companies listed on the IDX from 2017 to 2021 as the research sample. The data that has been collected is then tested using Eviews, using several tests which include, panel regression sample selection test, descriptive statistical test, partial test, multicollinearity test, panel regression goodness test, simultaneous test, classic assumption test which includes normality test & heteroscedasticity test. The results of this test determine that the variables Return on Assets, Return on Equity, Net Profit Margin, Debt to Equity have a positive & significant impact on profit growth in manufacturing agencies recorded on the IDX in 2017-2021